TERMINAL TIPE B DI ALALAK BERBASIS KONSEP CONNECTIVITY - Ramadhan, Risky Ihsan; Hadinata, Irwan Yudha (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Banjarmasin as the capital city of South Kalimantan currently has excellent economic growth potential. The potential is utilized by the government with the Banjarbakula Metropolitan Area program that unites Banjarmasin - Banjarbaru - Banjar Regency - Barito Kuala Regency - Tanah Laut Regency into one national strategic area. To realize this Metropolitan Area program, transportation facilities such as terminals that can accommodate various modes of transportation are needed for better accessibility between cities or regencies, especially Barito Kuala Regency. However, terminals are often to have some problems such as conflicting circulation either human circulation or vehicle circulation as well as less integrated function. To solve that problem, Alalak Type B Terminal using Connectivity concept that focus on good connectivity on circulation and accessibility. To combine these connectivity, superimposition methods are eventually used to integrate various circulation as well as function into one whole unit to create well-organized circulation without conflict and with integrated function.